1990
DOI: 10.1111/j.1365-2958.1990.tb00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a cryptic crystal protein gene of Bacillus thuringiensis subspecies kurstaki by gene fusion and determination of the crystal protein insecticidal specificity

Abstract: DNA hybridization with the insecticidal crystal protein gene cryllA (formerly cryBl) of Bacillus thuringiensis supspecies kurstaki has shown that subspecies kurstaki contains a cryllA-related sequence in addition to the cryllA gene (Donovan et al., 1988a). We have cloned the cryllA-related sequence and have determined that the sequence, which has been designated cryllB, is 89% identical to the cryllA gene. Recombinant B. thuringiensis cells harbouring the cloned cryllB gene produced very little CryllB protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 17 publications
1
60
0
1
Order By: Relevance
“…In this study, the toxic isolate Bt117-4 showed cuboidal crystals, which are known to contain proteins toxic to Lepidoptera (Dankocsik et al, 1990;Wu et al 1991;Monnerat et al, 2007;Silva-Werneck and Ellar, 2008).…”
Section: Discussionmentioning
confidence: 78%
“…In this study, the toxic isolate Bt117-4 showed cuboidal crystals, which are known to contain proteins toxic to Lepidoptera (Dankocsik et al, 1990;Wu et al 1991;Monnerat et al, 2007;Silva-Werneck and Ellar, 2008).…”
Section: Discussionmentioning
confidence: 78%
“…Cry2Aa2 (referred to as Cry2Aa for brevity) was purified from Escherichia coli that produced Cry2Aa protoxin inclusion bodies (21). The Cry2Aa used in diet bioassays and the Cry2Ab in plants (formerly called CryIIA and CryIIB, respectively) have 88% amino acid identity (5). In pairwise comparisons against five lepidopteran pests, the median lethal concentrations of Cry2Aa and Cry2Ab differed by 1.1-to 5.8-fold against any particular pest (5).…”
Section: Aphis-s Azp-ro (F16) Mov97 (F24) Mov97-r (F24) and Azp-rmentioning
confidence: 99%
“…Cry2Ab is toxic to some lepidopteran larvae, including the major cotton pests Heliothis virescens and Helicoverpa zea (5). The efficacy of Cry2Ab against pink bollworm has not been reported previously, but the closely related B. thuringiensis toxin Cry2Aa is highly effective against pink bollworm (14,34).…”
mentioning
confidence: 99%
“…This promoter region induces Cry1A expression in B. thuringiensis cells under sporulation conditions and was shown to have driven expression activity in Escherichia coli (20) that affects construction of Cry1Mod toxins (data not shown). In this work, we replaced the cry1Ab promoter region with another promoter region that would not be expressed in E. coli, as was shown for the cry3Aa promoter region that induced the expression of Cry2Ab in B. thuringiensis cells but not in E. coli cells (21). We show here that under this expression system, cry1AMod gene constructs are efficiently produced.…”
mentioning
confidence: 88%